Research on bank financing strategy of e-commerce supply chain driven by blockchain - Yang, Lei; Hou, Qiaoming (Frontiers in Physics, 2025)
IntroductionIn the e-commerce supply chain, many risk-averse suppliers face the dilemma of capital constraints. Bank financing helps to alleviate these financing difficulties, and blockchain trust mechanisms can optimize bank financing strategies.MethodsTo address the issue of capital constraints for suppliers, based on the two operating modes of Consignment and Direct Selling in the e-commerce supply chain, using the Stackelberg game, considering the company’s risk-averse behavior and consumers’ green preferences, a game model is constructed to explore the impact of factors such as blockchain, risk aversion, product greenness, guarantee interest rates, and information verification efforts on bank financing strategies.Results and discussionWhen the blockchain technology is adopted within a certain threshold, the supplier can obtain higher financing income by adopting consideration than Direct Selling. Compared with the Direct Selling mode, the blockchain trust mechanism under consideration mode can play a better role and improve the financing efficiency of suppliers. The financing efficiency of suppliers will also decrease with the increase of risk aversion coefficient, and the impact of risk aversion on suppliers will be greater in the case of blockchain, but the trust of blockchain will increase with the increase of risk aversion coefficient. Product greenness will increase the sales price of e-commerce supply chain under consideration mode, and improving product greenness will help improve enterprise cash flow. However, under the Direct Selling mode, the impact on the price is not great, and the impact on the financing strategy will be different. Although the guaranteed interest rate will increase the financing cost, it will make banks more willing to provide financing for suppliers with financial constraints. In practice, managers should comprehensively consider the balance between guaranteed interest rate and financing return. Information verification efforts will increase product greenness and green preference coefficient, and the improvement of information transparency will make e-commerce platforms more willing to provide guarantees for suppliers. This study is expected to provide decision-making references for the managers of e-commerce supply chain.